The Effect of Perturbation-Based Balance Training and Conventional Intensive Balance Training on Reactive Stepping Ability in Individuals With Incomplete Spinal Cord Injury or Disease: A Randomized Clinical Trial - Unger, Janelle; Chan, Katherine; Lee, Jae W.; Craven, B. Catharine; Mansfield, Avril; Alavinia, Mohammad; Masani, Kei; Musselman, Kristin E. (Frontiers in Neurology, 2021)
Introduction: Impaired balance leads to falls in individuals with motor incomplete spinal cord injury or disease (iSCI/D). Reactive stepping is a strategy used to prevent falls and Perturbation-based Balance Training (PBT) can improve this ability. Objective: The objective of this study was to determine if PBT results in greater improvements in reactive stepping ability than frequency-matched Conventional Intensive Balance Training (CIBT) in adults with iSCI/D. Design: Randomized clinical trial. Setting: Tertiary SCI/D rehabilitation centre. Participants: Twenty-one adults with chronic (>1 year) iSCI/D were randomized. Due to one drop out 20 participants completed the study. Methods: Participants were randomly allocated to complete either PBT or CIBT three times per week for eight weeks. Both programs included challenging static and dynamic balance tasks, but the PBT group also experienced manual external balance perturbations. Main Outcome Measures: Assessments of reactive stepping ability using the Lean-and-Release test were completed at baseline, and after four and eight weeks of training, and three and six months after training completion. A blinded assessor evaluated secondary outcomes. Results: Twenty-five participants were screened and 21 consented; one withdrew. Ten PBT and 10 CIBT participants were included in analyses. Across all participants there were improvements in reactive stepping ability (p=0.049), with retention of improvements at follow up assessments. There were no differences in reactive stepping ability between groups (median (interquartile range): PBT 0.08 (0.68); CIBT 0.00 (0.22)). One participant in the PBT group experienced a non-injurious fall during training. Conclusions: Balance training is beneficial for individuals with iSCI/D, but the addition of manual perturbations (i.e. PBT) did not prove advantageous for performance on a measure of reactive stepping ability. Trial Registration Number: NCT02960178